Show that tan(θ) + cot(θ) = sec(θ)csc(θ)

Expert Answers

An illustration of the letter 'A' in a speech bubbles

You also may use the alternative approach, such that:

`cot theta = 1/tan theta`

Replacing `1/tan theta` for `cot theta` yields:

`tan theta + 1/tan theta = sec theta csc theta`

Bringing the terms to the left side to a common denominator, yields:

`(tan^2 theta + 1)/tan theta = sec theta csc theta`

Using the trigonometric identity `tan^2 theta + 1 = sec^2 theta` yields:

`(sec^2 theta)/tan theta = sec theta csc theta`

Reducing duplicate factors both sides yields:


(The entire section contains 2 answers and 219 words.)

Unlock This Answer Now

Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Start your 48-Hour Free Trial
Approved by eNotes Editorial Team